COVID-19 with acute hepatitis A virus co-infection in a fully-vaccinated individual: a case report - Masra Lena Siregar; Rabid Yahya Putradasa; Arini Nisaul; Suheir Muzakkir (School of Medicine, Universitas Syiah Kuala, 2021)
In a developing country with varying degree of public hygiene and sanitation, prevalent infectious diseases such as hepatitis A (HAV) could add to the burden of infection during coronavirus disease 2019 (COVID-19) pandemic and complicate its gastrointestinal and hepatic manifestation. Here we present a case COVID-19 with acute hepatitis A virus co-infection in a young female with fever, joint pain, non-productive cough, loss of smell, abdominal discomfort, darkened urine, and pale loose stool before admission. The significant finding was slightly icteric sclera, hepatomegaly with tenderness in the epigastrium and right upper quadrant, increase in aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total bilirubin, C-reactive protein and, D-dimer. A naso-oropharyngeal swab examination for SARS-CoV-2 infection was positive, and IgM anti-HAV was reactive with a total anti-HAV titer 60 mIU/mL. Subsequently, she was hospitalized for 14 days, successfully recovered; her symptoms resolved and her level of liver enzymes back to normal, and she was discharged for self-isolation at home. RT-PCR for SARS-CoV-2 infection came back negative 7 days later. In light of the pandemic, physicians need to raise suspicion of co-infection of COVID-19 with other hepatitis viruses in cases with gastrointestinal and hepatic manifestation. A marked increase in liver enzyme may warrant further testing for hepatitis viruses where such infection should be suspected.